2009
DOI: 10.1016/j.jjcc.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiac rehabilitation in patients with metabolic syndrome after coronary artery bypass grafting

Abstract: These results suggest that CR might be useful for patients with MetS after CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 34 publications
2
34
0
1
Order By: Relevance
“…Patients in the supervised exercise group had significant improvements in triglyceride, LDL-cholesterol and HDL-cholesterol, whereas the home-based group showed improvement in HDLcholesterol only. In a recent study, Onishi et al 29 also reported CR exercise training might improve LDL-cholesterol and total cholesterol in CABG patients with metabolic syndrome. Additionally, metabolic scoring defined by the number of the modified Adult Treatment Panel criteria of the US National Cholesterol Education Program was significantly improved.…”
Section: Lipid Profilementioning
confidence: 94%
See 1 more Smart Citation
“…Patients in the supervised exercise group had significant improvements in triglyceride, LDL-cholesterol and HDL-cholesterol, whereas the home-based group showed improvement in HDLcholesterol only. In a recent study, Onishi et al 29 also reported CR exercise training might improve LDL-cholesterol and total cholesterol in CABG patients with metabolic syndrome. Additionally, metabolic scoring defined by the number of the modified Adult Treatment Panel criteria of the US National Cholesterol Education Program was significantly improved.…”
Section: Lipid Profilementioning
confidence: 94%
“…After training, the v  O 2peak and peak lower limb torques significantly increased, and the circumferences of thigh and calf were also increased. In a recent study, Onishi et al 29 reported a 6-month aerobic and resistance training program also improved v  O 2peak and isokinetic peak torques of knee extensor and flexor in patients after CABG. It appears that a combined aerobic and resistance training program significantly increased exercise tolerance and lower limb muscle strength.…”
Section: Muscular Strengthmentioning
confidence: 96%
“…Regular physical exercise is associated with a reduction of inflammatory markers and ischemic events in patients with CAD. 25) We also found that CR for 6 months ameliorated inflammatory states in patients with metabolic syndrome after CABG 14) and that voluntary exercise improves the progression of endothelial dysfunction and atherosclerotic lesion formation through anti-inflammatory effects in an experimental study. 26) In the present study, the change of plaque volume and vessel remodeling did not differ significantly between the PII-CR and non PII-CR groups.…”
Section: Discussionmentioning
confidence: 57%
“…Rehabilitation protocol: The CR program consisted of warmup stretching, aerobic exercise, resistance training, and a cooldown, and was scheduled once or twice weekly for 6 months as described. 14,15) Briefly, about 60 minutes of aerobic exercise consisted of cycling on an ergometer and walking on a treadmill and on an indoor track. The exercise intensity was prescribed at the anaerobic threshold (AT) of each individual determined by ergometry using expiratory gas analysis or at a value of 11-13 on the standard Borg rating of perceived exertion (RPE) scale.…”
mentioning
confidence: 99%
“…Although various studies were conducted to test the effect of CR on MetS patients, there are still inconsistent results on the effect of CR on reverse MetS and also its components. For instance, although several studies have failed to find any significant effect of CR on high density lipoprotein cholesterol (HDL-C),[161718] some others have even documented its significant effects on HDL-C.[19202122] The same pattern can be observed in other metabolic factors too. [161718192021222324252627282930] Therefore, the present article aimed to summarize and if possible, perform a meta-analysis on published data about the effect of CR on MetS reduction rate and its components or related metabolic and anthropometric markers.…”
Section: Introductionmentioning
confidence: 99%